2017
DOI: 10.1039/c7ra02317k
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of partially sulfonated low density polyethylene (LDPE) membranes as separators in microbial fuel cells

Abstract: Sulfonated low density polyethylenes (LDPEs) in varied molar ratios have been analyzed as separating barriers in microbial fuel cells (MFCs) for bioelectricity production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…All these results suggest that DHN-70 can be used as alternate membrane material to Nafion 117 in an MFC application. In addition, the membranes prepared in this investigation showed better results in terms of power density as compared to many other hydrocarbon based membranes when incorporated in MFC. However, it is always not possible to compare the membrane performance owing to different fuel cell configurations and their operating conditions. ,, …”
Section: Resultsmentioning
confidence: 86%
“…All these results suggest that DHN-70 can be used as alternate membrane material to Nafion 117 in an MFC application. In addition, the membranes prepared in this investigation showed better results in terms of power density as compared to many other hydrocarbon based membranes when incorporated in MFC. However, it is always not possible to compare the membrane performance owing to different fuel cell configurations and their operating conditions. ,, …”
Section: Resultsmentioning
confidence: 86%
“…Besides, promising outcomes have been reported with the already commercialized CMI-7000 as an alternative to Nafion [114][115][116][117][118][119][120]. Furthermore, particular studies demonstrated the potential of PBI [77], SPPS [121], SLDPE [122], SPVDF [123], crosslinked and sulfonated PVA [124] for membrane manufacturing and application in BES. Moreover, blend membrane preparation has been investigated too, based on the mixture of polymers such as PVA-SA-PEG [125], SPEEK-PES [126], PES-SPES [127].…”
Section: Sufficient Geometrical Traits (Area Thickness Surface Morpmentioning
confidence: 99%